2018
DOI: 10.1089/jop.2017.0085
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Excitatory Amino Acid Transmission in the Retina: Studies on Neuroprotection

Abstract: Excitotoxicity occurs in neurons due to the accumulation of excitatory amino acids such as glutamate in the synaptic and extrasynaptic locations. In the retina, excessive glutamate concentrations trigger a neurotoxic cascade involving several mechanisms, including the elevation of intracellular calcium (Ca and the activation of α-amino-3-hydroxy 5-methyl-4-iso-xazole-propionic acid/kainate (AMPA/KA) and N-methyl-d-aspartate (NMDA) receptors leading to retinal degeneration. Both ionotropic glutamate receptors (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 140 publications
0
17
0
1
Order By: Relevance
“…14,15 In the eye, excitotoxicity has been linked to glaucoma, retinal ischemia, and diabetic retinopathy. [16][17][18][19][20] Indeed, high concentrations of glutamate or NMDA delivered via intravitreal injections can be utilized as a tool to cause RGC death in vivo. [21][22][23][24][25][26] We performed a single intravitreal injection of 10 nmol of NMDA in adult mice and analyzed NMDA-induced RGC death at two different time points (day 1 [d1] and day 7 [d7]) (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…14,15 In the eye, excitotoxicity has been linked to glaucoma, retinal ischemia, and diabetic retinopathy. [16][17][18][19][20] Indeed, high concentrations of glutamate or NMDA delivered via intravitreal injections can be utilized as a tool to cause RGC death in vivo. [21][22][23][24][25][26] We performed a single intravitreal injection of 10 nmol of NMDA in adult mice and analyzed NMDA-induced RGC death at two different time points (day 1 [d1] and day 7 [d7]) (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Some reports have indicated that all iGluRs are expressed in the retinal neuron cultures, while NMDARs are mainly responsible for glutamate induced retinal neurons death (Otori et al, 1998; Fang et al, 2010). Others have reported that non-NMDARs (AMPAR/KAR and mGluRs) also play key roles in glutamate mediated cell death in cultured retinal neurons (Dhingra and Vardi, 2012; Opere et al, 2018). To uncover the mechanism of Pin1 activation induced by glutamate, the distinct GluR subtypes involved in the glutamate-induced, first, retinal RN should be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that retinal neurons express all of the glutamate receptor subtypes (Luo et al, 2001; Fang et al, 2010). Some reports have indicated that retinal excitotoxicity was mediated by both non-NMDAR and NMDAR, whereas other studies have found an entirely non-NMDAR-mediated retinal neuronal death (Luo et al, 2001; Opere et al, 2018). Such differences may be partially due to the maturational changes of retinal neurons and the difference in cell culture environment (Luo et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, despite welladjusted IOP, 15% of glaucoma patients become blind and as many as 42% lose sight in one eye [31]. In this regard, growing evidence obtained from both animal models and clinical studies has revealed risk factors other than elevated IOP and aging, which include vascular dysfunction [32][33][34][35], glutamate excitotoxicity [36][37][38], mitochondrial dysfunction [39][40][41], and oxidative stress [13,14,[42][43][44]. Given its higher prevalence, a vast proportion of studies attempting to decipher the association between oxidative stress and glaucoma have focused on POAG.…”
Section: Glaucomamentioning
confidence: 99%